Peningkatan Kesadaran Remaja tentang Bahaya Narkoba untuk Membangun Generasi yang Sehat dan Bebas Zat Adiktif - Bassam; Agus Kurnia; Zidan Akbar Abhinaya; Lenny Herlina (Insan Kreasi Media, 2024)
Drug abuse among adolescents is a serious problem that threatens the future of the young generation and public health. The prevalence of drug use in Indonesia, especially among students, continues to increase, so education and socialization about the dangers of drugs are very important. This community service program is carried out at SMAN 1 Batu Layar with the aim of increasing students' understanding of the dangers of drugs and forming an anti-drug attitude. The methods used include lectures, interactive discussions, and simulation activities that actively involve students, creating an engaging learning atmosphere. The results of the activity showed a significant improvement in student understanding, where the percentage of students who did not understand decreased from 26% to 9%, and students who understood very well increased from 23% to 29%. The conclusion of this service emphasizes that the socialization program implemented is effective in increasing student awareness. With better knowledge, students are expected to become agents of change in their communities and contribute to the prevention of drug abuse, demonstrating the importance of collaboration between schools and communities in creating a safe and healthy environment for the younger generation.